Characterization of pig farming in Paraíba State, Brazil (Research, Society and Development, 2023)
The objective of this research was to characterize pig farming in the different mesoregions of Paraíba State. The data were obtained through the Official Veterinary Service, by structured questionnaires based on knowledge acquired during visits to the production units (PU). It were evaluated 3,561 PU, of which 1,174 in the Sertão Paraibano (SP), 1,034 in Borborema (B), 1,088 in Agreste Paraibano (AP) and 265 in Mata Paraibana (MP). Pig farming in Paraíba is characterized by many small PUs, with an average activity time of 12.2 years. The PU are located mainly in the countryside and practice subsistence artisanal pig farming. They are individual creations, where the system of pigsties/pens predominates, production by complete cycle and termination. The source of water used in the activity depends on the availability and geoclimatic conditions of the mesoregions. Waste is disposed of mainly in the open. In SP and AP, the walls of the premises are predominantly wooden, the type of floor is mainly clay and the roof of the premises is made of tile or straw. The properties of MP stood out from the others due to the higher percentage of masonry walls, lesser number of wire or wood walls, predominantly cement floor and tile coverage. The structure of farms in the MP indicates PUs that are more technically and appropriate to animal safety and welfare standards. The results of this research are useful for disease control programs, identify flaws or distinction in the animal managements and can assist in the improvement of pig farming.